A mediação do bibliotecário na pesquisa escolar face a crescente virtualização da informação - Bicheri, Ana Lúcia Antunes de Oliveira [UNESP] (2008)
In parallel with the advancement of technology and use of the term the knowledge society, realizes it is people who do not know sign to the satisfaction surveys and readings. Some teachers and school librarians concern itself only with the guidance in the acquisition of skills for the use of technological resources in tracking information. Forget that the environment of the library, more than its physical space, must reach the homes of students, classrooms and other contributions of teaching materials. Therefore, it is answering questions such as: The librarian knows who is a mediator? As has been the mediation? The librarian accompanies technological change, inserting them into their daily lives do? The virtualization of the information facilitates the use of sources / resources research and the ability to select information and expand knowledge? The study aimed to: assess the perception of the librarian as its responsibility in daily mediate the search school, regardless of the environment in which it is; examine the attitude and technical skills / knowledge of the librarian in mediation of the search in a time of growing virtualization of documents; verify the process of the use of technological resources in the search for information; identify the existence of partnership between librarian and professor in the practice of research school; obtain subsidies for proposals for projects / activities aimed at finding solutions to the search school reaches its objectives. Intent is a theoretical through the relevant literature and to collect data applied to be a focused interview with the professional librarian in six schools of basic education of the city of Londrina.